2005
DOI: 10.1002/cncr.21589
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial of valproic acid and all‐trans retinoic acid in patients with poor‐risk acute myeloid leukemia

Abstract: BACKGROUND Valproic acid (VPA), a histone deacetylase (HDAC) inhibitor, induced in vitro differentiation of primary acute myeloid leukemia (AML) blasts, an effect enhanced by all‐trans retinoic acid (ATRA). Clinical responses to VPA were recently observed in patients with myelodysplastic syndrome (MDS). Herein, the authors have described results of a clinical trial with VPA plus ATRA in 26 patients with poor‐risk AML. METHODS VPA (5–10 mg/kg starting dose) and ATRA (45 mg/m2) were administered orally. Low‐dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
127
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(128 citation statements)
references
References 22 publications
0
127
1
Order By: Relevance
“…53 These findings underscore the potential of novel epigenetic approaches in transplantation, gene, and neurological therapies. Bug et al 54 reported that the combination of VPA with all-trans retinoic acid is effective in patients with advanced acute myeloid leukemia, leading to blast cell reduction and improvement of hemoglobin. Investigation of the effect of VPA on normal hematopoietic stem cells (HSC) shows that the drug increases both proliferation and selfrenewal of HSC.…”
Section: Conjugation Products Of Valproic Acid and Neuroinhibitory Ammentioning
confidence: 99%
“…53 These findings underscore the potential of novel epigenetic approaches in transplantation, gene, and neurological therapies. Bug et al 54 reported that the combination of VPA with all-trans retinoic acid is effective in patients with advanced acute myeloid leukemia, leading to blast cell reduction and improvement of hemoglobin. Investigation of the effect of VPA on normal hematopoietic stem cells (HSC) shows that the drug increases both proliferation and selfrenewal of HSC.…”
Section: Conjugation Products Of Valproic Acid and Neuroinhibitory Ammentioning
confidence: 99%
“…HDACi, for example, the hydroxamic acid-based vorinostat (SAHA, Zolinza), are promising drugs for cancer treatment (Richon et al, 1998;Marks and Breslow, 2007). Several HDACi are in phase I and II clinical trials, being tested in different tumor types, such as cutaneous T-cell lymphoma, acute myeloid leukemia, cervical cancer, etc (Bug et al, 2005;Chavez-Blanco et al, 2005;Kelly and Marks, 2005;Duvic and Zhang, 2006) (Table 2). Although considerable progress has been made in elucidating the role of HDACs and the effects of HDACi, these areas are still in early stages of discovery.…”
Section: Introductionmentioning
confidence: 99%
“…Selection of the respective DACi doses was based on previously proven inhibition of deacetylase activity in primary AML progenitor cells and clinical relevance. 4,19 DACi treatment efficiently inhibited proliferation of LAFP-as well as mock-transduced 32D cells by the factor 5-21 compared with untreated controls (Fig. 1C).…”
Section: Introductionmentioning
confidence: 87%
“…DACi additionally induce selective proteasomal degradation of histone decetylase 2 (HDAC2), DNA methyltransferases and other proteins responsible for aberrant gene repression and signaling. [4][5][6] This effect equally alters the cellular program, but to date, the underlying mechanisms remain elusive and have not yet been studied in the leukemic stem and progenitor compartment.…”
Section: Introductionmentioning
confidence: 99%